Marine Skeletal Biopolymers and Proteins, and Their Biomedical Application - Rahman, Azizur (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book covers recent trends in all aspects of basic and applied scientific research on marine skeletal proteins and biopolymers (e.g., chitin, collagen), and their derivatives. Some recent innovations of marine proteins have been incorporated in this book that could be potentially applied in scientific and industrial research. Due to their broad array of biological functions in biopolymer- and protein-based drugs, such as anticancer, antimicrobial, bone tissue regeneration, antioxidant, and anti-aging functions, bioactive skeletal proteins and biopolymers have recently attracted a great amount of interest in the pharmaceutical, nutraceutical, and cosmeceutical industries (including anti-aging drugs).